The product of the nuclear gene PET309 is required for translation of mature mRNA and stability or production of intron-containing RNAs derived from the mitochondrial COX1 locus of Saccharomyces cerevisiae. - Manthey, G M (1995)
Expression of the Saccharomyces cerevisiae mitochondrial COX1 locus, which contains several introns and is co-transcribed with the downstream genes AAP1, OLI2 and ENS2, is controlled by at least 18 nuclear-encoded proteins. The PET309 gene, encoding one of these proteins, was cloned, sequenced and shown to contain an open reading frame of 965 codons. Isonuclear PET309+ and delta pet309::URA3 strains carrying mitochondrial genomes that differ in the number of COX1 introns, were generated. Analysis of RNA species from these strains demonstrated an inverse relationship between the number of introns present in the precursor RNA and the amount of COX1 and AAP1/OLI2/ENS2 RNAs accumulated in a pet309 mutant. Hence, PET309 plays a role either in transcription of intron-containing primary transcripts from the COX1-AAP1-OLI2-ENS2 transcription unit or in stabilization of primary transcripts. PET309 is also required in translation of COX1 mRNA. A mitochondrial bypass suppressor of the pet309 deletion mutation was isolated, and shown to consist of a DNA rearrangement at the COX1 locus, such that the 5' untranslated leader region (UTR) of the COB gene was fused to COX1 at nucleotide -174 of its 5' UTR. This result suggests that Pet309p acts through the COX1 5' UTR to activate initiation of translation of the COX1 coding region.